Financing of the Operations of Retail Chains - Ignatova, Nikolinka (Research Papers, 2025)
This study examines the state and changes in the financing of the operations of retail chains in the Republic of Bulgaria. The focus of the research is on retail chains for fast-moving consumer goods, furniture and interiors, household appliances (both black and white goods), and fashion items. These include: „Kaufland Bulgaria“ Ltd., „Lidl Bulgaria“ Ltd. & Co. K.D., „Metro Cash and Carry Bulgaria“" Ltd., „Aiko“ Ltd., „House Market Bulgaria“ AD, „Mömax Bulgaria“ Ltd., „Zora M.M.S.“ Ltd., „Technomarket Bulgaria“ AD, „Technopolis Bulgaria“ AD, „H&M Hennes & Mauritz“ Ltd., „Zara Bulgaria“ Ltd., and „Peek & Cloppenburg“ Ltd. The subject of the research is the composition and structure of the financing sources for the operations of retail chains, which include equity, current liabilities, and non-current liabilities. The study assesses the coverage ratios – the ratio of borrowed capital to equity, debt capital to equity, long-term assets to equity, long-term assets to long-term financing sources, and the weighted average cost of capital. A comparative analysis and statistical methods are applied. The limiting conditions relate to the time period of the study, which spans from 2017 to 2021, and the entities under investigation, which are twelve retail chains in the Republic of Bulgaria.